Truth and History in Vico and Betti - Gaspare Mura (Critical Hermeneutics, 2023)
This paper, written at the invitation of Giuliano Crifò (1934-2011), former extraordinary Assistant of Emilio Betti (1957-1960), and President of the Emilio Betti Institute at La Sapienza in Rome since 1987, presents Giovanni Battista Vico as the founder of the veritative hermeneutics in the modern age. His vision of the hermeneutics of history, based on the verum ipsum factum and on the perspective of the meta-historical dimension of Providence, lies far from the Hegelian immanentist declinations. The, the paper compares Vico's perspective with the canons of veritative hermeneutics of the jurist Emilio Betti, a great representative of the hermeneutic debate of the twentieth century. Betti links hermeneutics to the question of truth, the primary object of hermeneutics itself. In the debate of the twentieth century, Betti is one of the greatest defenders of Vico's intuition. Vico’s and Betti’s hermeneutic account can help us confront the weak thinking in the contemporary philosophical context.